File Encryption and Decryption Using Algorithm Aes-128 Bit Based Website - Irwanto, Dola (Institut Riset dan Publikasi Indonesia, 2024)
Digital data security has become very important in the current information era. One way to maintain data security is to use encryption and decryption techniques. The Advanced Encryption Standard (AES) algorithm has been proven effective in protecting data with a high level of security. This research aims to implement the AES-128 bit algorithm for online file encryption and decryption via a website. The method used in this research includes developing a website that provides a user interface for uploading and encrypting files, as well as for decrypting files that have been previously encrypted. The AES-128 bit algorithm is used to carry out the file encryption and decryption process. Users can choose their own encryption key or use a random key generated by the system. The result of this research is a website that can be used to efficiently secure sensitive files using the AES-128 bit algorithm. By using this website, users can easily encrypt the files they want to protect and also decrypt files that have been encrypted previously. The security of user data is guaranteed through the use of strong encryption algorithms and well-managed keys.